Antibacterial Potential of Seagrass Cymodocea Rotundata (Alismatales: Cymodoceaceae) Extract on The Pathogenic Bacteria Staphylococcus Aureus - Almira Fardani Lahay; Muhammad Kholiqul Amiin (Jurnal Biologi Tropis, 2023)
Staphylococcus aureus is classified as a pathogenic bacterium in humans and animals. S. aureus infection in humans can cause skin infections, and produce toxins that result in shock syndrome, foodborne disease, bacteremia, endocarditis, metastatic infections, and sepsis, while in milk-producing animals it can cause mastitis infection. Initially, S. aureus can be overcome with penicillin antibiotics but often develops time S. aureus becomes resistant to penicillin to cause new infections, namely the Methicilin Resistant Staphylococcus aureus (MRSA) which was first reported in 1961. One of the natural ingredients from the sea that has natural antibacterial content is seagrass or Cymodocea rotundata. Which is one type of seagrass in Indonesia that is included in the round type of grass. Cymodocea rotundata has bioactive components such as alkaloids, flavonoids, phenol hydroquinone, steroids, triterpenoids, tannins, and saponins that function as antibacterials. This study aims to determine the potential of seagrass Cymodocea rotundata as an antibacterial against Staphylococcus aureus bacteria. This research is experimental research using wells. Samples of Cymodocea rotundata seagrass came from the coastal waters of Ketapang and were converted into a simplified powder form with ethanol solvent. The results showed that the diameter of the inhibition zone formed ranged from 5.5 mm - 9.7 mm, the largest in the 40% treatment. Based on this research, it can be concluded that the extraction of seagrass Cymodocea rotundata has benefits as an antibacterial and potential in the field of pharmacology.